Single-Industry Regions of Russia: Determination, Typology and Prospects of Development - Zaynutdinov, Ruslan Raisovich (Economy of Regions, 2015)
For a long period, in the Russian economy, mainly the issues of the location of production and achievement of maximum efficiency from the industrial policy were carried out, which led to the formation of single-industry regions with disproportions in socio-economic development. Today, as in the previous world financial and economic crisis of 2008-2009, the problems grow worse for the single-industry regions of Russia due to their narrow sectoral specialization. The poorly diversified economic structure of the single-industry regions, the reduction of prices for output products, a high dependence on foreign technologies under the natural resource depletion are being the strong deterrent to the development of single-industry regions. Therefore, the need to place special emphasis on identifying the ways to diversify and modernize these regions becomes obvious. The article presents the genesis of the single-industry territories of Russia with the allocation of essential characteristics and problems that prevent the development of single-industry regions. The special attention is paid to the dominating industries determining the regional features of the socio-economic development of these regions. Therefore, the algorithm of determination and classification of the single-industry regions of Russia has been developed and approved. The world experience of modernization and reconstruction of the single-industry regions was analyzed. Recommendations for improving the efficiency of the state policy concerning the single-industry regions on the basis of using the potential of small businesses with the large industry enterprises are proposed. Revealed features of the single-industry regions of Russia allow to draw the conclusion that for the further balanced development of these regions, it is necessary to use entirely new approaches that take into account particular characteristics of the industry, accumulated problems and the current foreign economic position of the Russian Federation.